Improved ventilatory response during exercise over time after concussion: A case report. Issue 3 (16th February 2023) - Welch, Ryan; Kelly, Brooke; Whyte, Ken; Ellyett, Kevin; King, Clair
Abstract: This case study reports the exercise ventilatory responses of a 17‐year‐old female who sustained a traumatic brain injury (TBI) which resulted in loss of consciousness. Subsequently, she suffered from post‐concussion syndrome accompanied by orthostatic and exercise intolerance. A cardiopulmonary exercise test (CPET) was performed 2 years post‐TBI. The results demonstrated significant hypoventilation with elevated PetCO2 and ventilatory equivalents, progressive desaturation, and pre‐syncope symptoms limiting exercise capacity. A repeat CPET 4 years post‐TBI demonstrated a similar exercise capacity limited by pre‐syncope symptoms. However, there was a marked improvement in the ventilatory response, with appropriate ventilation, PetCO2, and ventilatory equivalents, and only minor desaturation near peak exercise. Hypoventilation during exercise has been reported in subjects with post‐concussion syndrome; however, with time the exercise ventilatory response can potentially normalize as observed in this subject. Abstract : Our case report details the ventilatory response during exercise of a 17‐year‐old female who suffered a sports related concussion and subsequently post‐concussion syndrome. On exercise test 1 (two‐years following concussion), the striking abnormality was hypoventilation, however on repeat exercise test two‐years later the ventilatory response was normal. Improved ventilatory response following concussion may be related to improved CO2 sensitivity or neuroplasticity remodelling the ventilatory response during exercise.